Learning Strategies for Islamic Religious Education for Mentally Disabled Students in State Junior High Schools Extraordinary - Jakarta - Mukhtar, Muallim (The International Journal of Education Management and Sociology, 2023)
The purpose of this research is to find out (1). Procedures for learning Islamic religious education for mentally disabled students at State SLB (2). The strategy applied in the learning process of Islamic religious education for mentally disabled students at State SLB (3). Islamic spiritual education learning method for mentally disabled SLB Negeri - Jakarta students. Research Methods Using descriptive qualitative theory describes the phenomena occurring in research locations. The data collection technique involved interviews with subject teachers, teaching staff, and parents. Documentation studies in the form of official notes at meetings, archives, and literacy related to learning, observations at research locations at SLB Mental Disability. Conclusion The learning procedure consists of initial, core, and final activities, with preparation before the learning process is carried out. Doing prayer learning and training on cognitive aspects, teachers with expository and contextual learning strategies. Learning methods through lectures, questions and answers, demonstrations, and exemplary. The media used in learning are prayer equipment, sarongs for male students, makes for female students, prayer mats, and places for ablution. The evaluation was carried out through test and no-test techniques. The test techniques are written tests and oral tests. Obstacle factors in learning are limitations in remembering lessons, language limitations, lack of discipline, and the absence of accompanying teachers.